2021
DOI: 10.3390/plants10112468
|View full text |Cite
|
Sign up to set email alerts
|

Coco Peat as Agricultural Waste Sorbent for Sustainable Diesel-Filter System

Abstract: Oil spill incidents are hazardous and have prolonged damage to the marine environment. Management and spill clean-up procedures are practical and rapid, with several shortcomings. Coco peat (CP) and coco fibre (CF) are refined from coconut waste, and their abundance makes them desirable for diesel spillage treatment. Using a filter-based system, the selectivity of coco peat sorbent was tested using CP, CF and peat-fibre mix (CPM). CP exhibited maximal diesel sorption capacity with minimal seawater uptake, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 60 publications
(101 reference statements)
2
10
0
Order By: Relevance
“…When the reactive sites of sorbents were saturated with oil molecules, equilibrium was reached, and desorption occurred [51]. These findings revealed that the saturation of sorbent occurred at a 25% oil concentration, which coincides with the findings by Verasoundarapandian et al [7]. Figure 6.…”
Section: Effects Of Oil Concentration On Treated Efb Spikeletssupporting
confidence: 86%
See 4 more Smart Citations
“…When the reactive sites of sorbents were saturated with oil molecules, equilibrium was reached, and desorption occurred [51]. These findings revealed that the saturation of sorbent occurred at a 25% oil concentration, which coincides with the findings by Verasoundarapandian et al [7]. Figure 6.…”
Section: Effects Of Oil Concentration On Treated Efb Spikeletssupporting
confidence: 86%
“…Less availability of space compound at high packing density (0.11 g/cm 3 ) to adsorb oil is the main reason for the decrease in oil absorbed efficiency [48]. Similar observations have been reported previously by Verasoundarapandian et al [7], Taufik et al [11], Khalid et al [39] and Abel et al [49]. In addition, the development of porosity between the fibre was increased in a lower fibre packing density (0.06 and 0.07 g/cm 3 ) due to non-compacted samples having no sufficient capillary pressure to absorb oil [39,50].…”
Section: Effects Of Packing Density On Treated Efb Spikeletssupporting
confidence: 86%
See 3 more Smart Citations